Human papillomavirus insertions identify the PIM family of serine/threonine kinases as targetable driver genes in head and neck squamous cell carcinoma. (28th April 2020) - Broutian, Tatevik R.; Jiang, Bo; Li, Jingfeng; Akagi, Keiko; Gui, Shanying; Zhou, Zhengqiu; Xiao, Weihong; Symer, David E.; Gillison, Maura L.
Abstract: Human papillomavirus (HPV) insertions in cancer genomes have been linked to various forms of focal genomic instability and altered expression of neighboring genes. Here we tested the hypothesis that investigation of HPV insertions in a head and neck cancer squamous cell carcinoma (HNSCC) cell line would identify targetable driver genes contributing to oncogenesis of other HNSCC. In the cell line UPCI:SCC090, HPV16 integration amplified the PIM1 serine/threonine kinase gene ~16-fold, thereby increasing transcript and protein levels. We used genetic and pharmacological approaches to inhibit PIM kinases in this and other HNSCC cell lines. Knockdown of PIM1 transcripts by transfected short hairpin RNAs reduced UPCI:SCC090 viability. CRISPR/Cas9-mediated mutagenesis of PIM1 caused cell cycle arrest and apoptosis. Pharmacological inhibition of PIM family kinases decreased growth of UPCI:SCC090 and additional HNSCC cell lines in vitro and a xenograft UPCI:SCC090 model in vivo . Based on established interactions between intracellular signaling pathways and relatively high levels of gene expression in almost all HNSCC, we also evaluated combinations of PIM kinase and epidermal growth factor receptor (EGFR) inhibitors. Dual inhibition of these pathways resulted in supra-additive cell death. These data support clinical testing of PIM inhibitors alone or in combination in HNSCC. Highlights: HPV integrants in UPCI:SCC090 cells helped identify PIM serine/threonine kinases as targetable cancer driver genes in HNSCC. Genetic and pharmacological reductions in PIM kinase expression in HNSCC cells resulted in cell death in vitro and in vivo. PIM family kinases were found to be highly expressed in almost all head and neck cancers. Synergistic cell death occurred when EGFR inhibitors were combined with PIM kinase inhibitors. These findings strongly justify clinical trials of combined EGFR and PIM kinase inhibitors for recurrent or metastatic HNSCC.